Tourism and tourism spaces - Shaw, Gareth (SAGE, 2015)
Tourism and Tourism Spaces introduces students to the relationship between tourism, tourists, and the tourism spaces. The examination is at different levels - from local to global - and is informed by the discussion of three central processes: production, regulation, competition; consumption and commodification; and construction of tourist places and spaces.